Molecular Engineering of Tetracyclic 2, 3‐Dihydro‐1H‐benzo[2, 3]‐benzofuro[4, 5‐e][1, 3]oxazine Derivatives: Evaluation for Potential Anticancer Agents. Issue 10 (23rd August 2017) - Botla, Vinayak; Pilli, NavyaSree; Koude, Dhevendar; Misra, Sunil; Malapaka, Chandrasekharam
Abstract : Water‐mediated one‐pot Mannich type condensation of dibenzo[b, d]furan‐2‐ol with different amines resulted in a large library of novel 2, 3‐dihydro‐1 H ‐benzo[2, 3]benzofuro[4, 5‐e][1, 3]oxazine derivatives in moderate to excellent yields. The ortho‐ aminomethylation of the dibenzofuranols proceeded smoothly in the presence of various aromatic/aliphatic amines and paraformaldehyde, followed by cyclization. All the newly synthesized tetracyclic 2, 3‐dihydro‐1 H ‐benzo[2, 3]benzofuro[4, 5‐e][1, 3]oxazine derivatives were chemically characterized and screened for their cytotoxicity activity by cell viability assay (MTT test) against three human cancer cell lines and antibacterial activity by determining the minimum inhibitory concentration (MIC) against four bacterial strains. Among all the derivatives, MCV‐24 showed promising anticancer activity by inhibiting the cell proliferation of an ovarian cancer cell line (SKOV3) with an IC50 value at 7.5 µM, whereasMCV‐24 toMCV‐30 derivatives showed moderate activity against a lung cancer cell line (A549) with an IC50 value ranging from 11 to 15.9 µM. BesidesMCV‐29, ‐30, and‐31 also exhibited broad‐spectrum antibacterial activity. Among all new compounds, MCV‐24–30 showed promising anticancer andMCV‐29–31 antibacterial activity. Abstract : Water‐mediated one‐step Mannich type condensation of dibenzo[b, d]furan‐2‐ol with different amines gave a large library of novel 2, 3‐dihydro‐1 H ‐benzo[2, 3]benzofuro[4, 5‐e][1, 3]oxazine derivatives. Among these, MCV‐24 showed promising anticancer activity by inhibiting the cell proliferation of the SKOV3 ovarian cancer cell line at IC50  = 7.5 μM. DerivativesMCV‐24 toMCV‐30 showed moderate activity against the lung cancer cell line A549.